How do we actually put smarter snacks in schools? NOURISH (Nutrition Opportunities to Understand Reforms Involving Student Health) conversations with food-service directors - Rosenfeld, Lindsay E (Public Health Nutr, 2016)
OBJECTIVE: In autumn 2012, Massachusetts schools implemented comprehensive competitive food and beverage standards similar to the US Department of Agriculture’s Smart Snacks in School standards. We explored major themes raised by food-service directors (FSD) regarding their school-district-wide implementation of the standards. DESIGN: For this qualitative study, part of a larger mixed-methods study, compliance was measured via direct observation of foods and beverages during school site visits in spring 2013 and 2014, calculated to ascertain the percentage of compliant products available to students. Semi-structured interviews with school FSD conducted in each year were analysed for major implementation themes; those raised by more than two-thirds of participating school districts were explored in relationship to compliance. SETTING: Massachusetts school districts (2013: n 26; 2014: n 21). SUBJECTS: Data collected from FSD. RESULTS: Seven major themes were raised by more than two-thirds of participating school districts (range 69–100 %): taking measures for successful transition; communicating with vendors/manufacturers; using tools to identify compliant foods and beverages; receiving support from leadership; grappling with issues not covered by the law; anticipating changes in sales of competitive foods and beverages; and anticipating changes in sales of school meals. Each theme was mentioned by the majority of more-compliant school districts (65–81 %), with themes being raised more frequently after the second year of implementation (range increase 4–14 %). CONCLUSIONS: FSD in more-compliant districts were more likely to talk about themes than those in less-compliant districts. Identified themes suggest best-practice recommendations likely useful for school districts implementing the final Smart Snacks in School standards, effective July 2016.